2014
DOI: 10.1007/s10616-014-9788-y
|View full text |Cite
|
Sign up to set email alerts
|

The effects of different molecular weight chondroitin-4-sulfates in chondrocyte pellet culture

Abstract: For this study, we cultured chondrocyte pellets in Dulbecco's modified Eagle's medium plus a 2 % fetal bovine serum medium, and treated them with 2-to 8-mer oligosaccharides of chondroitin sulfate A to examine the effects of these oligosaccharides on the differentiation and protection of chondrocytes. We found low-molecular-weight CSAs to increase the ratio of the gene expression levels of collagen II/collagen I of chondrocytes from the first day up to 14 days after culture compared with those under a CSA-free… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 28 publications
0
1
0
Order By: Relevance
“… 36 , 37 Studies using CS alone have shown that CS has anti-inflammatory and chondroprotective actions. 38 - 40 …”
Section: Introductionmentioning
confidence: 99%
“… 36 , 37 Studies using CS alone have shown that CS has anti-inflammatory and chondroprotective actions. 38 - 40 …”
Section: Introductionmentioning
confidence: 99%